Infant and Toddler Consumption of a Lipid Nutrient Supplement After a 2-Week Home Repeated Exposure. (29th May 2020) - Johnson, Susan; Shapiro, Allison; Moding, Kameron; Davis, Kathryn; Montalvo, Allyson; Flesher, Abigail; Fisher, Jennifer
Abstract: Objectives: Repeated exposure (RE) paradigms produce improvements in food acceptance during infancy, however, less is known about RE effectiveness in toddlers. Here we examine the effects of RE on acceptance of sweetened and unsweetened versions of a lipid nutrient supplement (LNS). Methods: Mothers and children ( n  = 56, 86% NonHispanic White), aged 7–11.30 mo ( n  = 12; infants) and 12–24 mo ( n  = 44; toddlers), participated in a randomized, 2-week home exposure study and 2 lab visits (Baseline [V1] & Post-exposure [V2]). Children were randomized to RE of 1) sweetened or 2) unsweetened versions of the LNS mixed into oatmeal. At V1, mothers offered version 1 of LNS (sweetened or unsweetened) until the child took 2 bites or refused 3 times. Then mothers fed the alternate version ([HE]; the LNS to which children were randomized for home exposure) until the child refused to eat more. Intake (g) of HE was measured. Mothers were given 10 servings of the HE version and told to offer their child the 10 servings over the following 2-week period. At V2, mothers again fed unlimited amounts of HE until the child refused to eat more and intake in grams was again measured. A linear mixed model for repeated measures tested change in intake of HE across V1 and V2 by age group (toddlers v. infants) and by LNS version (sweetened v. unsweetened). Significance of the statistical interaction (visit by age group and visit by version) was defined at P  < 0.1. Results: Fifty-five dyads (98%) completed V1 and V2. Caregivers offered their children, on average, 9 of 10 possible home exposure servings. Observed intake of the HE differed by age group (infants, V1 = 32.3 g ± 15.8, V2 = 28.8 ± 20.9 vs. toddlers, V1 = 15.5 g ± 16.3 V2 = 23.9 ± 19.5; P  = .006). The linear mixed model confirmed (F = 3.41, P  = .07) that intake of HE significantly increased from V1 to V2 in the toddler group, whereas intake in the infant group remained consistent between V1 and V2. The unsweetened version was preferentially consumed compared to the sweetened version ( P  = .07). Conclusions: Children consumed the unsweetened version as well, if not better, than the sweetened version of the supplement. Over time, infants were consistent in their willingness to consume the supplement whereas toddlers showed an increase in intake, suggesting that toddlers may learn to eat the supplement through RE. Funding Sources: Global Alliance for Improved Nutrition.